A two alternative forced choice method for assessing vibrotactile discrimination thresholds in the lower limb. (3rd April 2019) - Iandolo, Riccardo; Carè, Marta; Shah, Valay A.; Schiavi, Simona; Bommarito, Giulia; Boffa, Giacomo; Giannoni, Psiche; Inglese, Matilde; Mrotek, Leigh Ann; Scheidt, Robert A.; Casadio, Maura
Abstract: The development of an easy to implement, quantitative measure to examine vibration perception would be useful for future application in clinical settings. Vibration sense in the lower limb of younger and older adults was examined using the method of constant stimuli (MCS) and the two-alternative forced choice paradigm. The focus of this experiment was to determine an appropriate stimulation site on the lower limb (tendon versus bone) to assess vibration threshold and to determine if the left and right legs have varying thresholds. Discrimination thresholds obtained at two stimulation sites in the left and right lower limbs showed differences in vibration threshold across the two ages groups, but not across sides of the body nor between stimulation sites within each limb. Overall, the MCS can be implemented simply, reliably, and with minimal time. It can also easily be implemented with low-cost technology. Therefore, it could be a good candidate method to assess the presence of specific deep sensitivity deficits in clinical practice, particularly in populations likely to show the onset of sensory deficits.